2014
DOI: 10.1002/cite.201300132
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a New Technique to Measure the Coefficient of Restitution for Nanoparticles

Abstract: A modified single‐stage low pressure impactor is described to measure the coefficient of normal restitution en for nanoparticles. The device is analysed numerically using CFD, and the gas flow inside the structured impaction plate is studied. A formula for the calculation of en is derived and first measurements of en for spherical silver particles are presented together with numerical data obtained from force‐based molecular dynamics simulations. Furthermore, the simulation data for en and the sticking probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…We investigate the collision of a nanoparticle with a solid adhesive wall by means of molecular dynamics. It was shown that MD simulations of low-pressure impaction deliver reliable results for the coefficient of restitution [20], well in agreement with experiments. The initial state is sketched in Fig.…”
Section: A Interaction Models and System Geometrysupporting
confidence: 65%
“…We investigate the collision of a nanoparticle with a solid adhesive wall by means of molecular dynamics. It was shown that MD simulations of low-pressure impaction deliver reliable results for the coefficient of restitution [20], well in agreement with experiments. The initial state is sketched in Fig.…”
Section: A Interaction Models and System Geometrysupporting
confidence: 65%
“…These results show that the AIS will have great utility for measuring the reflection of nanoparticles from surfaces, yielding quantitative information on the coefficient of restitution that describes the inelasticity of such collisions [29,30].…”
Section: Introductionmentioning
confidence: 85%
“…Modeling of this parameter for different particle materials enables understanding of key properties that affect a collision. Indirect observations of impact behavior at the nanoscale have also been reported using extrapolations and modeling to determine particle velocities that are otherwise challenging to detect. Previous work and modeling at the nanoscale is particularly focused on understanding the effects of nanoscale properties on collisions commonly described with continuum mechanics for larger particles. Therefore, most of these previous studies have been confined to collisions of particles <100 nm in diameter where deviations from bulk material properties have been noted. , Examination of particles in the 100–1000 nm diameter range provides information about the transition from a bulk description of particle properties down to the nanoscale.…”
Section: Introductionmentioning
confidence: 99%